Pengaruh Pendapatan Non Halal, Zakat, dan Dewan Pengawas Syariah terhadap Reputasi Bank Syariah: Studi Perbandingan Bank Umum Syariah di Indonesia dan Malaysia Periode 2018-2024 - Wiwit Putri Utami; Wahyu Iryana; Rahmat Fajar Ramdani (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
The growth of the Islamic banking industry requires these institutions to not only focus on their financial performance, but also maintain their reputation as a reflection of social legitimacy and public trust. This study aims to analyze the effect of non-halal income, zakat, and the Sharia Supervisory Board (DPS) on the reputation of Islamic Commercial Banks (BUS) in Indonesia and Malaysia for the period 2018–2024. This study uses a comparative quantitative approach with a purposive sampling method targeting 7 BUS in Indonesia and 6 BUS in Malaysia and analyzed using multiple linear regression. The results show that in Indonesia, non-halal income has no significant effect on reputation, while zakat and DPS have a positive and significant effect. In Malaysia, non-halal income has a negative and significant effect on reputation, while zakat and DPS have a positive and significant effect. These results indicate that compliance with sharia and corporate governance play an important role in building the reputation of Islamic banks, with differences in influence influenced by regulatory characteristics and supervisory systems in each country.